Tratamento do zumbido: comparação entre terapia de habituação e de mascaramento - Paula Isabela Trindade de Andrade (2018)
Introduction: Tinnitus is an auditory sensation that does not come from the external environment and can be perceived in one or both ears. It is a symptom of high prevalence that affects the adult population. Its pathophysiology is multifactorial, and may be associated with hearing loss due to aging, exposure to high intensity noises or to the use of ototoxic agents. Its mechanism of perception begins in the peripheral auditory pathways towards the auditory cortex reaching other non-auditory centers, such as the limbic system and the Autonomic Nervous System. The constant perception of tinnitus added to this dynamic interaction of some centers of the central nervous system triggers negative reactions and of annoyance with tinnitus, being this mechanism the neurophysiological model of perception of tinnitus. The audiological evaluation of the individual with tinnitus should be composed of anamnesis, vocal audiometry and conventional tonal audiometry, which evaluates the auditory thresholds in the frequencies from 250 Hz to 8000 Hz. High frequency audiometry has been considered an important tool for investigation and early detection of hearing loss related to several factors, among them aging, exposure to noise and ototoxic drugs. Studies have shown that the high frequency thresholds are related to the discrimination of sounds and speech recognition. Several therapeutic approaches to tinnitus treatment have been proposed, among them masking therapy and tinnitus therapy, with no proven evidence regarding the superiority of one technique or another for tinnitus relief. It is known that the guidelines should be associated with all approaches, as they help to break the cycle of activation of the limbic system loops of the neurophysiological model, and generate behavioral and reflexive changes in the individual. Objectives: To analyze the auditory thresholds of high frequencies of individuals with tinnitus, to verify the association of these thresholds with the main complaints and to compare the benefit of Habituation Therapy and Masking Therapy in the treatment of tinnitus. Methods: Two studies were performed. The first was a cross-sectional study of 39 adults. A conventional and high frequency audiological evaluation was performed, besides objective and subjective evaluation of tinnitus. For the comparison between masking therapy and tinnitus habituation, a longitudinal quasi-experimental study was carried out, composed of 33 adult individuals. An evaluation of tinnitus was carried out using anamnesis, conventional and high frequency tonal threshold audiometry, Otoacoustic Emissions research, Tinnitus Handicap Inventory (THI), evaluation of tinnitus annoyance through the Visual Analogue Scale (EVA) acufenometry and minimum level of masking. Subjects were randomly assigned to two groups. Group 1 was composed of 16 individuals submitted to Habituation Therapy, and group 2 was composed of 17 individuals submitted to Masking Therapy for 12 months. At the end, all subjects were reassessed using THI and EVA and the results were compared between groups. Statistical analysis was performed considering a significance level of 5% in all analyzes. Results: The first study had 39 participants, 16 men and 23 women with a mean age of 64.9 years. There was no association between the presence of auditory symptoms and auditory thresholds at high frequencies in subjects with tinnitus. The sample of the second study consisted of 33 adults with a mean age of 66.09 years. Both in the group submitted to Habituation Therapy and in the group submitted to Masking Therapy, there was a statistically significant improvement in relation to the annoyance and the impact of tinnitus on the individuals' quality of life. Conclusions: Individuals with tinnitus have associated symptoms such as sensitivity to intense sounds, dizziness, vertigo and atrial fullness, regardless of gender. In the studied sample, there was no association between the hearing loss side and the tinnitus side, confirming the possibility of a central perception of tinnitus. Tinnitus therapy and masking therapy were effective in reducing the perception of tinnitus and reducing its impact on quality of life. There was no significant difference between the two groups, evidencing the importance of counseling and monitoring the patient with tinnitus to change the negative attitudes generated by this symptom. Key words: Tinnitus, Audiometry, Pure tone audiometry, Hearing loss, hearing aids, therapy, masking.